The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0032321715614012
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Making through Facebook Engagement: Young Citizens’ Political Interactions in Australia, the United Kingdom and the United States

Abstract: The emergence of personalised, interactive forms of social media has led to questions about the use of these platforms for engagement in politics. Existing research focuses on whether political actors successfully engage citizens, and how social media platforms mobilise young people into offline participation. In this article, we present original survey data on how many young people use social media to do politics: share information, express themselves, and take action. Everyday Facebook use is underpinned by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 39 publications
0
49
1
6
Order By: Relevance
“…As is widely acknowledged in political science, political participation is not limited to the ballot box (Hayward 2006;Milbrath 1965;Verba, Schlozman and Brady 1995;Vromen et al 2016). No political scientist would claim that voting is the only significant form of political participation.…”
Section: Modes Of Political Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…As is widely acknowledged in political science, political participation is not limited to the ballot box (Hayward 2006;Milbrath 1965;Verba, Schlozman and Brady 1995;Vromen et al 2016). No political scientist would claim that voting is the only significant form of political participation.…”
Section: Modes Of Political Participationmentioning
confidence: 99%
“…Drawing on various NZES questions, we find that in New Zealand in 2014 young people were significantly less likely to believe that their votes would 'count', a little less likely to believe that voting makes a difference and that who is in power can make a difference, and a little more likely to believe that globalisation reduces government's 'room for manoeuvre'. Qualitative analysis could no doubt provide further evidence and insight (for example, Vromen et al 2016). Lower turnout might also relate to more rational decisions about the lack of electoral competitiveness in 2014 or a sense that few of the parties had much to offer younger voters.…”
Section: Modes Of Political Participationmentioning
confidence: 99%
“…Moeller et al found that exposure to digital news influenced their political participation, and developed their sense of civic duty and information efficacy. In another study, Vromen, Loader, Xenos, and Bailo (2016) surveyed young people in Australia, the United Kingdom, and the United States of America, and found that social media had become a regular source of information on politics and that youth engagement through social media is a form of political participation worthy of our attention. Glynn's (2006) "Critical Appraisal Checklist" confirmed that this study was valid in several areas: Institutional Review Board approval was received, and focus group interview and essay questions were provided.…”
Section: Commentarymentioning
confidence: 99%
“…In the recent digital politics and movements literature, there is an over-reliance on platforms that are mainly public facing and where the application programming interface can be accessed to create more complete datasets; thus, a focus on Twitter and distributed petitioning sites. Yet, most ordinary citizens are still much more likely to use Facebook, and various studies consistently show that it is the leading social media platform for accessing everyday information on news and politics (Reuters Institute 2015; Vromen et al 2016). It is possible, however, to focus on public or community Facebook pages (see e.g.…”
Section: Digital Campaigning: Facebookmentioning
confidence: 99%